Electronic controller system - Muhammad Hafizol , Husain (2010)
Technologies of remote access have been effectively used in various fields of engineering for a long period of time, Network communications have made the technology of remote access available for a great deal of applications. Remote access can be used in practice - control and monitoring of electric and election dëvicës, whereby an operator can control the device at a distance and get back a response with experimental data; This project is to design and develop a prototype of electronic controller system that has facilities such as lighting, Air-conditioner and Security System (CCTV. All these facilities will lid contf011ed either by software setting or manually controlled in case there are system malfunction in auto mode. Signals from all these facilities will be fed into appropriate controller and then will be sent to server for data processing using parallel port cable. Server will be remote by client in other place to control the ECS appli"tioii in the saffid Of iOäi aIea network (LAN).